Tales from a not-so-dorky drama queen - Russell, Rachel Renée; Russell, Erin (Russell, Rachel Renée. Dork diaries, 2015)
Middle schooler Nikki Maxwell's worst nightmare is realized when her frenemy Mackenzie gets ahold of her top secret diary.